Effects of Two Salts Compounds on Mycelial Growth, Sporulation, and Spore Germination of Six Isolates of Botrytis cinerea in the Western North of Algeria - Boualem Boumaaza; Mohamed Benkhelifa; Moulay Belkhoudja (International Journal of Microbiology)
Six isolates of Botrytis cinerea were isolated from leaves and stems of different tomato varieties taken from four areas in the northwest of Algeria where tomato is mostly grown in greenhouses and high tunnels. The purpose of this research was to determine the effect of two salts, NaCl and CaCl2, on three stages of Botrytis cinerea’s life cycle. All isolates tested were stimulated in 50 to 150 ppm; NaCl was the most effective treatment to increase mycelial growth at two tested concentrations. However, at 300 ppm concentration, CaCl2 completely inhibited the growth of mycelium; they reach 34.78% for the isolate TR46 and 26.72% for isolate F27. The sodium and calcium salts stimulated conidia production in liquid culture. We noticed that the effect of calcium chloride on sporulation was average while sodium chloride. In the medium containing 50 ppm, calcium chloride and sodium chloride increased the germination capacity of most isolates compared with the control. Other calcium salts, at 100 or 300 ppm, decreased the germination percentage of the conidia. With the exception of sodium salts, the inhibitions of germination reduce at 150 or 300 compared with the control. Conidial germination was slightly inhibited by sodium chloride only when the concentration was over 300 ppm.